(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Organization in the creative industry face increasingly competitive challenges. This increasingly challenges makes organizations have to find ways to survive and if possible, win and prosper. Competitiveness is largely determined by the capabilities that can be owned by the organization. One, among other factors, that can produce capability is through the formation of appropriate cultural factors. Market orientation and entrepreneurship orientation are cultures that can trigger capabilities. This capability will be fostering creativity in responding to environment changes that occur, which in turn will greatly affect organizational performance. This study was conducted in the fashion creative industry in Bandung, West Java. A total 160 research samples from the fashion creative industry were obtained. This study found that market orientation and entrepreneurship orientation as cultural factors, have positive and significant effect on marketing performance.